(untitled) (Bangladesh Heart Journal, 2021)
Digitalis glycosides are among the oldest drugs used in cardiology. Nowadays, due to the limited indications for their use (advanced heart failure, usually concomitant with atrial fibrillation), cases of toxicity induced by this class of drugs are rarely observed. Digoxin produces a positive inotropic and bathmotropic effect on the heart, but has a negative chronotropic and dromotropic effect. Cardiac glycosides have a narrow therapeutic window, so digitalis treatment can easily lead to symptoms of overdose. In patients taking digoxin, the drug therapeutic level should be maintained at 1-2 ng/ml; the toxic effects occur at concentrations > 2.8 ng/ml and are mainly related to disturbances of cardiac function and of the circulatory system, as well as gastrointestinal symptoms and CNS disturbances. Here, a 65-years-old patient who was hospitalized following chronic ingestion with acute renal impairment. In spite of rapidly applied gastric irrigation and administration of activated charcoal, the drug level in the patient’s blood was estimated at 8.5 ng/ml. During her stay on the ward, typical symptoms of severe toxicity were observed: from gastric symptoms (severe nausea, vomiting) to conduction disturbances. Type I, moitz type 1 and 2 AV blocks were detected, as well as some supraventricular extrasystoles. These conduction disorders required the use of temporary endocardial pacing. Due to the unavailability of specific antidotes (antidigitalis antibodies) and lack of efficient methods of extracorporeal elimination of the drug, symptomatic treatment comprising the correction of electrolyte disturbances and heart rate control remains the most effective. Bangladesh Heart Journal 2021; 36(2): 139-144